Development of Sales Employee Monitoring System in Integrated Performance Measurement Using Prototyping Method - Taufiqurrochman, Taufiqurrochman; Suryantoro, Hari; Hasibuan, Tuhfatul Habibah (Sean Institute, 2024)
Measuring employee performance is a critical component of ensuring the success and sustainability of a business in a competitive and dynamic business environment. The objective of this research is to create a web-based employee performance monitoring information system that can address the obstacles associated with managing employee performance, including data inaccuracy, reporting delays, and a lack of visibility of employee progress. The prototype method was employed to design this system, which enables the system to be developed iteratively in response to user feedback. This system's primary capabilities include the ability to access and revise employee data, prospects, and performance reports in real-time. The black box testing method was employed to evaluate the implementation of this system, and the results indicated that all of the features that were developed were valid and functioning properly. Ultimately, this system will facilitate more appropriate decision-making and increase company productivity by enabling companies to more effectively monitor employee performance. In summary, the information system for monitoring employee performance that has been developed provides a practical and effective solution to the numerous obstacles that organizations encounter when administering their performance.